KEANEKARAGAMAN POHON PELINDUNG DI KAMPUS UNIVERSITAS NEGERI PADANG DAN MANFAATNYA - Anisa Syahrul Rahmi; Moralita Chatri (Universitas Cokroaminoto Palopo, 2026)
The diversity of shade tree on campus plays an important role in supporting ecological, aesthetic, and educational functions of the environment. This study aimed to identify the species, number of individuals, and potential uses of tree-like plants at Padang State University campus. The study was conducted in December 2025 using survey and direct field observation methods with a qualitative descriptive approach. Species identification was based on plant morphological characteristics with the assistance of literature and plant identification applications. The results showed 1.544 tree individuals belonging to 26 species from 17 families. The most dominant species was Leucaena leucocephala, followed by Pterocarpus indicus, Terminalia catappa, Terminalia mantaly, and Veitchia merillii. The high diversity was influenced by habitat heterogeneity, tropical climate conditions, and variations in soil physical and chemical properties. The presence of tree vegetation contributes to improved air quality, microclimate regulation, CO₂ absorption, and habitat provision for other organisms. The UNP campus area has a high diversity of tree-like plants and plays an important role in supporting the sustainable management of campus green open spaces.